2022
DOI: 10.3390/d14030208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Landscape and Local Factors on the Diversity of Flower-Visitor Groups under an Urbanization Gradient, a Case Study in Wuhan, China

Abstract: Urbanization is one of the primary forces driving worldwide pollinator decline. Moderate urban expansion with appropriate green space planning can help in maintaining pollinator diversity and pollination service. We investigated the relative effects of landscape and local factors on the diversity of flower-visitor functional groups in a moderately urbanized city, Wuhan, located in central China. We found that the proportion of impervious surface had no significant effect on the number of visitations, but it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…This may indicate a very strong local filtering effect in the structure of butterfly communities 92 , 93 . Similarly, to hoverflies, butterflies benefited from high vegetation 36 , 94 . Butterfly species require plant structures for larval development and therefore rely on habitats with a sufficient amount of plant biomass and vegetation structure 36 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate a very strong local filtering effect in the structure of butterfly communities 92 , 93 . Similarly, to hoverflies, butterflies benefited from high vegetation 36 , 94 . Butterfly species require plant structures for larval development and therefore rely on habitats with a sufficient amount of plant biomass and vegetation structure 36 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of insect diversity in urban areas (city parks, campuses, etc.) of China have shown that the improvement of the quality of green spaces (higher plant species richness and flower density) and the use of attractive native flowering plants can help reduce the negative effects of city expansion on pollinator diversity [14,82,88,[110][111][112]. Therefore, treating urban scenic spots and roads as 'hotspots' for insect conservation and properly managing green spaces within them could be an effective way to benefit the survival of urban butterfly species [113,114].…”
Section: Urban/campus Disturbance and Butterfly Diversitymentioning
confidence: 99%
“…Plant diversity enrichment management is particularly beneficial for natural enemies or other beneficial insects by providing energyrich nectar, a widely utilized food source for various insect orders, including Diptera, Coleoptera, and Hymenoptera (Nilsson et al 2016). Additionally, plant diversity enrichment contributes to local-level diversity (He et al 2022;Schmack and Egerer 2023). Increasing landscape complexity, achieved through composition, configuration, or heterogeneity changes, significantly and positively impacts biodiversity.…”
Section: Introductionmentioning
confidence: 99%